2021
DOI: 10.3390/diagnostics11040720
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of 18F-FDG PET/CT Imaging over Modified Duke Criteria and Clinical Presumption in Patients with Challenging Suspicion of Infective Endocarditis

Abstract: According to European Society of Cardiology guidelines (ESC2015) for infective endocarditis (IE) management, modified Duke criteria (mDC) are implemented with a degree of clinical suspicion degree, leading to grades such as “possible” or “rejected” IE despite a persisting high level of clinical suspicion. Herein, we evaluate the 18F-FDG PET/CT diagnostic and therapeutic impact in IE suspicion, with emphasis on possible/rejected IE with a high clinical suspicion. Excluding cases of definite IE diagnosis, 53 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…VHI and RCR also follow an increasing tendency. As stated in the literature [ 28 30 ], uptake with homogeneous distribution throughout the valve is interpreted as inflammatory, due to a physiological phenomenon of foreign body reaction (macrophages reacting to prosthetic material without infection and without damage to the tissue). Conversely, irregular uptake with foci of increased metabolic activity in one or more areas of the periprosthetic tissue is interpreted as a focus of infection.…”
Section: Discussionmentioning
confidence: 99%
“…VHI and RCR also follow an increasing tendency. As stated in the literature [ 28 30 ], uptake with homogeneous distribution throughout the valve is interpreted as inflammatory, due to a physiological phenomenon of foreign body reaction (macrophages reacting to prosthetic material without infection and without damage to the tissue). Conversely, irregular uptake with foci of increased metabolic activity in one or more areas of the periprosthetic tissue is interpreted as a focus of infection.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in cases of PVE high uptake near the area of the valve was reported to be a marker of high embolic risk warranting early surgical intervention. 7 Using mDC the clinical probability of IE can be low or high, adding FDG PET/CT in the diagnostic workup of 53 patients with a possible diagnosis of IE, Valentin et al 7 reported that it helped in reclassifying Duke 1 cases as Duke 0 or Duke 2 with a sensitivity of 79 %, specificity of 100 %, positive predictive value (PPV) of 100 % and negative predictive value (NPV) of 89 % based on the final diagnosis confirmed by the Institutional multidisciplinary endocarditis team ( Table 1 ). Similar observations were reported by others, that the addition of FDG PET/CT to standard workup has enhanced the detection of 15–32 % additional foci 8 , 9 , 10 , 11 and the number needed to test was only 7 for this additional detection.…”
Section: Imagingmentioning
confidence: 99%
“…This test is devoid of nephrotoxicity and covers the area of interest ie the heart and also extra-cardiac structures and even it can pick up extra-cardiac sources of infective foci. By integrating this test with mDC, Valentin et al 7 could confirm definitive diagnosis of IE in 36 % of their cases and excluded in the rest 64 %. They classified cases into 4 categories.…”
Section: Indications For Fdg Pet/ct Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In 2015, the European Society of Cardiology (ESC) revised guidelines that highlight the importance of imaging in the management of patients with suspected IE. Indeed, new techniques are increasingly being used when TTE/TEE results are negative with a persistent high level of clinical suspicion [ 14 ]. Nuclear molecular imaging techniques provide additional value in diagnosing patients with possible IE using the modified Duke criteria.…”
Section: Clinical Perspectivesmentioning
confidence: 99%